Studi Literatur: Penyakit Menular Seksual - Irfan Syazali Nasution; Anisya Trihapsari; May Sarah Dianti; Nayla Nazwa; Sadza Raisya Haniya Nasution; Shela Ananta; Siti Mautia Saragih (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Background: Sexually Transmitted Infections (STIs) represent a global public health challenge. The increasing number of Sexually Transmitted Infection (STI) cases is a serious concern worldwide. A lack of education or minimal knowledge, along with risky behavior, contributes significantly to the high STI rates, particularly among the young age group. Purposes: The objective of this study is to conduct a comprehensive analysis of the major types of Sexually Transmitted Infections (STIs)—namely Gonorrhea, Hepatitis B, HIV/AIDS, Syphilis, and HPV—by identifying their risk factors and determining the most effective prevention strategies. Method:The researchers employed a literature review method. The data search process was conducted systematically on Google Scholar, limiting sources only to articles available in full text and having open access. Results: The literature review concludes that the factors of knowledge, attitude, behavior, and age significantly influence an individual's risk of contracting Sexually Transmitted Infections (STIs). Therefore, prevention efforts must be carried out comprehensively, encompassing promotive (awareness enhancement), preventive (prevention), curative (treatment), and rehabilitative (recovery) activities. Practically, this prevention must include sexual health education, adoption of safe sexual behavior, implementation of routine health checks (screening), and vaccination (specifically for Hepatitis B and HPV). Conclusion: Overall, controlling the spread of STIs requires active and collaborative roles from all parties—including the government, health workers, and the community. The main key to suppressing the spread and burden of STI diseases in the community is through improving appropriate sexual health education, improving access to health services, and periodic health screening.